2004
DOI: 10.1080/16501970310021383
|View full text |Cite
|
Sign up to set email alerts
|

A specific arm-interval exercise program could improve the health status and walking ability of elderly patients after total hip arthroplasty: a pilot study

Abstract: Preliminary results indicate that the improvement in physical fitness and functional status of the training group seems to be associated with better health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 4 publications
1
55
0
2
Order By: Relevance
“…Those two subjects did not complete the 1-year follow-up. Altogether, our interval-training program was able to induce an improvement in upper-body aerobic capacity, walking ability, and subjective health status (WOMAC score) [7][8][9]. In the walking tests, the TG covered a longer walking distance with a faster walking speed and with a longer stride length, and the cadence was higher (data not shown).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Those two subjects did not complete the 1-year follow-up. Altogether, our interval-training program was able to induce an improvement in upper-body aerobic capacity, walking ability, and subjective health status (WOMAC score) [7][8][9]. In the walking tests, the TG covered a longer walking distance with a faster walking speed and with a longer stride length, and the cadence was higher (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…We recently reported that a 6-week upper-limb interval training starting early after THA had positive effects in the recovery of elderly patients with osteoarthritis (OA) [7][8]. The positive effects of this aerobic training were observed 2 months after surgery on cardiorespiratory fitness, subjective health status (Western Ontario and McMaster University [WOMAC]), and walking ability THA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectiveness of physical rehabilitation for THR patients following discharge from hospital is supported by evidence [10-14]; however, the quality of existing trials prevents robust conclusions on the optimal content of rehabilitation programs. Recommendations regarding content include arm ergometer interval exercise [10], aerobic type dance routines [15], various strength and range of motion (ROM) exercises with and without resistance [11-13,16,17], and walking programs [13,17]. Existing literature also varies with respect to the quantity, timing to commencement, and frequency of physiotherapy rehabilitation [10-13,15-23].…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations regarding content include arm ergometer interval exercise [10], aerobic type dance routines [15], various strength and range of motion (ROM) exercises with and without resistance [11-13,16,17], and walking programs [13,17]. Existing literature also varies with respect to the quantity, timing to commencement, and frequency of physiotherapy rehabilitation [10-13,15-23]. Frequency ranges from twice daily [21] to twice weekly [15], and timing to commencement from immediately following hospital discharge [11] to greater than 6 months after [15,21].…”
Section: Introductionmentioning
confidence: 99%